Trabalho & ritual: o sentido da ritualização da morte para os profissionais do serviço funerário - Francisco, Vinícius Nascimento (2022)
The objective of this doctoral thesis is to understand the meaning that funeral service professionals attribute to the ritualization of death as an object of work in their daily lives. Historically, funerary rituals construct unique spaces and times for the normative absorption of death, through the ritualistic consecration of the bodies of the dead, thus seeking to reconcile man, shaken by the annihilation of his being, with the world, which naturalizes the death. In modernity, this immanent meaning of the funerary ritual remains intact, the dead continue to be veiled, buried or cremated, but what can be said about the meaning of the ritualization of death as the reproduction of their own daily life? What is at stake is not the reconciliation of man with the world, but the daily support of the ritualistic consecration of the dead through the rationalization of work in capitalism. In order to carry out such an undertaking, five funeral service workplaces were selected: Ideal Funeral Home, outsourced drivers, Perus Cemetery, Gethsemani Cemetery and the Vila Alpina Crematorium. Regarding the methodology adopted, semi-structured interviews were carried out only with funeral service professionals who work directly with the ritualization of the bodies of the dead (funeral agents, administrators, drivers, speedsters, burial workers, cremators), as well as the systematic observation of their routine of work. In this way, the research focused on the way in which such workers are socialized in the guidelines of funeral work: recruitment and division of labor. What was discovered, in this socialization process, is the incorporation of the rational look of the work around the ritualistic funeral practices (the ritualization of death seen from a common place and the body of the deconsecrated dead), which manages to apprehend precisely its loss of meaning for modern society – the dehumanization of funeral ritual (contempt for the dead, loss of family ties). Funeral service professionals, however, humanize themselves in the face of men's alienation from the ritualistic sense of dying in modernity. The representation of the ritualization of death ultimately becomes a reflection on life